Introducing MINA-The Molecularly Imprinted Nanoparticles Assay - Shutov, Roman V.; Guerreiro, Antonio R.; Moczko, Ewa; Perez De Vargas Sansalvador, Isabel M.; Chianella, Iva; Whitcombe, Michael J.; Piletsky, Sergey A. (Wiley, 2014)
A new ELISA‐ (enzyme‐linked immunosorbent assay)‐like assay is demonstrated in which no elements of biological origin are used for molecular recognition or signaling. Composite imprinted nanoparticles that contain a catalytic core and which are synthesized by using a solid‐phase approach can simultaneously act as recognition/signaling elements, and be used with minimal modifications to standard assay protocols. This assay provides a new route towards replacement of unstable biomolecules in immunoassays.